1980
DOI: 10.1111/j.1365-246x.1980.tb04828.x
|View full text |Cite
|
Sign up to set email alerts
|

New inferences from higher mode data in western Europe and northern Eurasia

Abstract: Summary Stacking methods applied to wide arrays of long period stations provide a powerful tool to investigate the physical properties of the upper mantle by means of higher modes. In this paper, the UC‐diagram technique of Cara (1976) is applied to a subset of records first used by Nolet (1975, 1976) to determine the dispersion of higher Rayleigh modes in western Europe. For the fundamental and first higher modes, the phase velocities found in the present study are very similar to those first obtained by Nole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 36 publications
4
28
0
Order By: Relevance
“…Preliminary measurements (Dost 1986) indicated that, by using NARS, higher mode Rayleigh wave phase velocities can be obtained for frequencies up to 70mHz. In comparison to earlier measurements in Europe, including the Baltic shield (Nolet 1977;Cara, Nercessian & Nolet 1980), this is an extension of 30mHz towards the high frequencies. Inversion of the data set for isotropic shear wave velocity and density yielded a smooth shear wave velocity model without a clear Lehmann discontinuity, but with a possible steep positfie density gradient from 60 to 100 km depth.…”
Section: Introductionmentioning
confidence: 68%
“…Preliminary measurements (Dost 1986) indicated that, by using NARS, higher mode Rayleigh wave phase velocities can be obtained for frequencies up to 70mHz. In comparison to earlier measurements in Europe, including the Baltic shield (Nolet 1977;Cara, Nercessian & Nolet 1980), this is an extension of 30mHz towards the high frequencies. Inversion of the data set for isotropic shear wave velocity and density yielded a smooth shear wave velocity model without a clear Lehmann discontinuity, but with a possible steep positfie density gradient from 60 to 100 km depth.…”
Section: Introductionmentioning
confidence: 68%
“…Love-and Rayleigh-wave dispersions, respectively (Cara et al 1980). Birefringence of SKS-waves in southern Germany is also observed and studied by Kind et al (1985).…”
Section: )mentioning
confidence: 79%
“…Vinnik et a!. (1983) used nine different combinations of three P-wave velocity models (Vinnik & Ryaboy 1981;Masse & Alexander 1974;Given & Helmberger 1980) and three S-wave velocity models (Cara 1979;Brune & Dorman 1963;Cara, Nercessian & Nolet 1980) to estimate delay times for the P410s phase in north-eastern Eurasia and south-western US. They found that different combinations of these models result in a difference in the value of Tps of up to 1 s. Using the relationship Tp,=z(l/Vsl/Vp, we find that a 1 s difference in the delay time at the 410 km depth (assuming Vp= 10 km sC1 and Vs=5.5 km s-') corresponds to a 12 km difference in depth.…”
Section: Kpv Results For Obnmentioning
confidence: 99%